Relationship between CSR activity of Hungarian energy companies and Hungarian customers’ behavior - Putzer, Petra; Pavluska, Valéria; Szűcs, Krisztián; Törőcsik, Mária (Marketing & Menedzsment, 2019)
The study tries to identify the relationship between the CSR of Hungarian energy companies and the households’ traditional and alternative energy consumption. Beside ethics the corporate social responsibility is typically influenced by three main actors: companies, government and customers. The major actor of CSR is of course the corporate sector, but other influential factors also should be taken into account. If customers are really responsible, then real CSR can appear, but if customers are self-conscious, only shallow CSR actions will spread. The results show that in the energy sector the real, “deep” CSR could not spread because of the gap between the consumers’ positive attitude and their effective or real behavior. The results also imply that the implementation of shallow CSR is enough for the consumers.